Factors Affecting the Adoption of Malaria Interventions for Pregnant Women in Tanzania: Tanzania Demographic Health Survey 2022 - Nyamukondiwa, Melisa; Adisasmita, Asri C.; Mahkota, Renti; Betera, Same (Jurnal Epidemiologi Kesehatan Indonesia, 2024)
Tanzania is endemic to malaria and pregnant women due to their vulnerability are among the high-risk groups. The adoption of malaria interventions targeted to pregnant women is affected by a number of factors. A cross-sectional study using secondary data from Tanzania Demographic Health Survey (TDHS) for 2022 was used. A logistic regression was used for bivariate analysis to identify factors affecting the adoption of malaria interventions during pregnancy in Tanzania. Data from pregnant women between 15 to 49 years (N=1408) were analyzed in this study. Insecticide treated nets (ITNs) and intermittent preventive therapy in pregnancy using sulfadoxine-pyrimethamine (IPTp-SP) were the main malaria prevention methods identified from the TDHS 2022. The results showed that insecticide treated nets ownership (83.0%) and its usage (85.5% of those who had ITN) was relatively high among pregnant women. More than half of the pregnant women (60.6%) received IPTp-SP during pregnancy. Marital status (ORmarried compared to not married=1.60; 95% CI: 1.15-2.24), education (ORsecondary level and higher compared to no education=1.43; 95% CI: 1.04-2.00) and Antenatal Care (ANC) visits (ORat least four ANC visits compared to no ANC=2.60, 95% CI: 1.40-4.82), and higher level wealth status and parity had statistically significant association with higher odds of using ITN. Age (OR≥35 years compared to 15-19 years=0.15, 95% CI: 0.05-0.50), education level (ORsecondary level and higher compared to no school=0.47, 95% CI: 0.27-0.79) and wealth status (at all levels, compared to the poorest) had statistically significant association with lower IPTp-SP uptake. Antenatal care visits should be maximized as an opportunity to distribute insecticide treated nets, give intermittent preventive medicine and education on malaria prevention. Future research should conduct multivariate analysis to determine independent predictors.